2016
DOI: 10.14334/jitv.v21i2.1357
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes of liver tissue and serobiochemical relation in does with pregnancy ketosis

Abstract: ABSTRAKAzmi AFM, Ghani AAA, Saadan AS, Mokrish A, Lai KS, Zamri-Saad M, Zuki AB, Hassim HA. 2016. Perubahan histologi jaringan hati dan hubungan serum biokimia pada kambing yang mengalami kebuntingan ketosis. JITV 21(2): 96-100. DOI: http://dx.doi.org/10.14334/jitv.v21i2.1357Perubahan histologi hati kambing yang mengalami kebuntingan ketosis dikarakterisasi pada penelitian ini. Dua puluh kambing bunting pada hari ke-80 digunakan pada percobaan ini. Sepuluh kambing bunting diberi pakan rumput (Napier) dan konse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Diagnosis of clinical pregnancy toxemia is based on history, clinical signs of hepatic encephalopathy, and serum biochemical profiles (De Lima et al, 2012). A previous study showed that the detection of pregnancy toxemia could be determined by observing the changes of serum biochemical profiles in blood and clinical signs of pregnant goats (Azmi et al, 2016). On the other hand, Duffield et al (2009) concluded that subclinical pregnancy toxemia is a common metabolic disorder that affects goats in the transition period or in early lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of clinical pregnancy toxemia is based on history, clinical signs of hepatic encephalopathy, and serum biochemical profiles (De Lima et al, 2012). A previous study showed that the detection of pregnancy toxemia could be determined by observing the changes of serum biochemical profiles in blood and clinical signs of pregnant goats (Azmi et al, 2016). On the other hand, Duffield et al (2009) concluded that subclinical pregnancy toxemia is a common metabolic disorder that affects goats in the transition period or in early lactation.…”
Section: Introductionmentioning
confidence: 99%